Fabrication, performance evaluation, and optimisation of adsorptive ammonia removal using hollow fibre ceramic membrane: Response surface methodology approach - Adam, M.R. (Elsevier B.V., 2021)
This work aims to optimise the factors that affect the adsorptive removal of ammonia by natural zeolite hollow fibre ceramic membrane (HFCM) in a continuous crossflow system using surface response methodology (RSM). The adsorptive HFCM was first characterised using the scanning electron microscopy (SEM) and Fourier transform infrared (FTIR) spectroscopy prior to the adsorption process. A face-centred central composite design (CCD) was used to statistically visualise the interaction of the factors, namely feed pH, feed concentration, and HFCM dosage, with the response of water permeability and ammonia removal of the HFCM. The optimum conditions for the HFCM performance were feed pH of 7.04, feed concentration of 75.00 mg/L, and HFCM dosage of 0.35 g, with a desirability value of 0.953. The excellent ammonia removal performance (96.5) reveals that the HFCM possesses great potential to be developed as a synergised system that combines the adsorption and filtration of water. Â© 2021 Elsevier Inc.